Nucleophile- or light-induced synthesis of 3-substituted phthalides from 2-formylarylketones - Gerbino, Darío César (2012)
The surprisingly facile conversion (isomerization) of 2-formyl-arylketones into 3-substituted phthalides, as observed for the marine natural product pestalone and its per-O-methylated derivative, was investigated using a series of simple 2-acylbenzaldehydes as substrates. The transformation generally proceeds smoothly in DMSO, either in a Cannizarro-Tishchenko-type reaction under nucleophile catalysis (NaCN) or under photochemical conditions (DMSO, 350 nm). © 2012 American Chemical Society.